A IPB e sua teologia: calvinista, puritana, fundamentalista? Reflexões a partir da tradição reformada sobre eclesiologia e cultura no contexto brasileiro - Fontes, Marcello (2004)
This dissertation seeks to investigate the existence of a Brazilian Reformed Theology in the area of ecclesiology and its relation to culture by using the Presbyterian Church of Brazil as the object of investigation. The first part investigates how the reformer John Calvin was educated and how his humanism related to the teaching he developed, as also its possible application to Brazilian Reformed Theology, choosing common Grace to understand this relation to culture in seeking to understand how wide was its influence in his ecclesiology. In the second part, Calvinism, Puritanism and Neopuritanism are analyzed toward possible divisions or continuity. Such situations will be studied as a possible cultural influence of the practical rationalization of the Calvinists and of the relation of Calvin and the puritans with science. The third part presents Richard Shaull as a contradiction to the style of being reformed neopuritans , applical to a good part of the Brazilian reformed of the Presbyterian Church of Brazil, to the extent that he attempted to construct a Reformed Theology of Revolution that his followers, perhaps his major contribution, could transform into a Theology of Liberation. His ecclesiastical vision will be compared to that of Ashbel Green Simonton, pioneer of the Presbyterian Church of Brazil. The fourth and final part will study the construction of Reformed Theology in the Presbyterian Church of Brazil today, its possible relation to fundamentalism, beginning or not with the puritans, above all a real fear as to its Brazilianity, seeking ways to respond to the kind of ecclesiology the Reformed Theology of the Presbyterian Church of Brazil has produced.